Nazistowski okultyzm a niemiecka koncepcja narodu i wspólnoty - Drozdowicz, Jarema (Polskie Towarzystwo Religioznawcze, 2010)
Jarema Drozdowicz – NAZI OCCULTISM AND THE GERMAN TRADITION IN THE QUESTION OF NATION AND COMMUNITY The occult movement within nazism is a phenomenon that has to be understood in a broad-er context of a certain tradition of speaking on nation and community. This very manner of dis-cussion is linked to earlier processes and movements that took place in Germany in the 19th Cen-tury and early 20th Century. The German romantic ideology, as an opposition to the Enlightment and modernism, classic nationalism and racial concepts were put together in a specific worldview called völkisch ideology. This ideology together with the concept of pan-germanism were the most important factors of the emergence of nazi esoterics. Such authors as Guido von List and Jörg Lans von Liebensfels delivered the theoretical background for the movement, which later had been incorporated into nazi rhetorics on nation, culture and race. This article makes an attempt of understanding how these ideas worked in theory and praxis during the rule of the nazi regime and how nazi occultism affected the action in occupied Europe.